Proposed minimal standards for description of methanogenic archaea. Issue 4 (25th April 2023) - Prakash, Om; Dodsworth, Jeremy A.; Dong, Xiuzhu; Ferry, James G.; L'Haridon, Stephane; Imachi, Hiroyuki; Kamagata, Yoichi; Rhee, Sung-Keun; Sagar, Isita; Shcherbakova, Viktoria; Wagner, Dirk; Whitman, William B.
Abstract : Methanogenic archaea are a diverse, polyphyletic group of strictly anaerobic prokaryotes capable of producing methane as their primary metabolic product. It has been over three decades since minimal standards for their taxonomic description have been proposed. In light of advancements in technology and amendments in systematic microbiology, revision of the older criteria for taxonomic description is essential. Most of the previously recommended minimum standards regarding phenotypic characterization of pure cultures are maintained. Electron microscopy and chemotaxonomic methods like whole-cell protein and lipid analysis are desirable but not required. Because of advancements in DNA sequencing technologies, obtaining a complete or draft whole genome sequence for type strains and its deposition in a public database are now mandatory. Genomic data should be used for rigorous comparison to close relatives using overall genome related indices such as average nucleotide identity and digital DNA–DNA hybridization. Phylogenetic analysis of the 16S rRNA gene is also required and can be supplemented by phylogenies of the mcrA gene and phylogenomic analysis using multiple conserved, single-copy marker genes. Additionally, it is now established that culture purity is not essential for studying prokaryotes, and description of Candidatus methanogenic taxa using single-cell or metagenomics along with other appropriate criteria is a viable alternative. The revisions to the minimal criteria proposed here by the members of the Subcommittee on the Taxonomy of Methanogenic Archaea of the International Committee on Systematics of Prokaryotes should allow for rigorous yet practical taxonomic description of these important and diverse microbes.